Consumer behaviour in tourism - Horner, Susan, 1956-; Swarbrooke, John (London ; New York, NY : Routledge/Taylor & Francis Group, 2021)
"Now fully revised and updated, the fourth edition of this bestselling text provides students with a vital understanding of the nature of tourism and contemporary tourist behaviour. It also shows them how this knowledge can be used to manage and market tourism effectively in a variety of sectors of tourism including: tour operations, hospitality, visitor attractions, transport, retail travel, cruising and airlines. This fourth edition has been updated to include: New material on the impact of CT developments in tourism including social media, AR and VR, the links between climate change, sustainability and tourist behaviour, the impact of crises and natural disasters on tourism and the cruise industry Thirty brand new international case studies about topical issues such as: Airbnb, travel blogs, overtourism, COVID-19, the flight-shaming movement, wellness tourism, hunting and tourism, terrorism, dark tourism, the solo traveller, volunteer tourism, second home ownership, music festivals, pilgrimage tourism, film and tv induced tourism, and tourism in Antarctica New online resources including Power Point slides and a case archive Each chapter features conclusions, discussion points, essay questions and exercises to help tutors direct student-centred learning and allow the reader to check their understanding of what they have read. This book is an invaluable resource for students studying tourism"--
First and second editions entered under: Swarbrooke, John.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Consumer behavior; Tourism